Prevalence and aetiology of moderate and severe thrombocytopenia in a tertiary and quaternary centre in KwaZulu-Natal - Ayanda G. Jali (African Journal of Laboratory Medicine, 2020)
Background: Thrombocytopenia is a common haematological disorder, characterised by platelet counts below 150 × 109/L. The aetiology of thrombocytopenia is multifactorial; notably, in a misdiagnosis this condition may be due to pre-analytical laboratory artefacts. Knowledge about the common aetiology of thrombocytopenia will assist clinicians in decision-making and interpretation of laboratory tests and this may lead to prompt, adequate patient management and cost-saving measures.